2013
DOI: 10.1016/j.molstruc.2013.02.012
|View full text |Cite
|
Sign up to set email alerts
|

New insight into UO2F2 particulate structure by micro-Raman spectroscopy

Abstract: h i g h l i g h t s " Uranyl fluoride particles prepared via hydrolysis of UF 6 were deposited on metallic substrates for micro-Raman spectroscopy." New substrates enhanced Raman signal from the particles of the size below 1 lm." Raman shift of U-O symmetric stretching appeared at values 847/842/839 cm À1 due to gradual water absorption by UO 2 F 2 . " The smooth substrates fa cilitated the process of water saturation of deposited particulate uranyl fluoride. " UO 2 F 2 particles deposited of metallic surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…Methods that can non-destructively detect and characterize these compounds would be highly desirable to monitor process chemistry and to chemically identify any environmental contamination. While a variety of spectroscopic probes exist for detecting uranium, including fluorescence spectroscopy [9,10] and Raman spectroscopy [11,12], X-ray absorption techniques are advantageous in that they are element-specific and highly sensitive to physical and chemical structure. Soft X-rays-X-rays with an energy below 1 keV-are particularly useful because absorption edges in this regime show minimal lifetime broadening (0.1-0.3 eV) [13][14][15], and as a result sharper absorption peaks and greater chemical information can be obtained.…”
Section: +mentioning
confidence: 99%
“…Methods that can non-destructively detect and characterize these compounds would be highly desirable to monitor process chemistry and to chemically identify any environmental contamination. While a variety of spectroscopic probes exist for detecting uranium, including fluorescence spectroscopy [9,10] and Raman spectroscopy [11,12], X-ray absorption techniques are advantageous in that they are element-specific and highly sensitive to physical and chemical structure. Soft X-rays-X-rays with an energy below 1 keV-are particularly useful because absorption edges in this regime show minimal lifetime broadening (0.1-0.3 eV) [13][14][15], and as a result sharper absorption peaks and greater chemical information can be obtained.…”
Section: +mentioning
confidence: 99%
“…Micro‐Raman spectroscopy has been used to identify specific markers for UO 2 , UO 4 •4(H 2 O) and U 3 O 8 , among other compounds (Pointurier and Marie , Stefaniak et al . ). For uranyl compounds, the vibrational spectra can change subtly depending on the co‐ordination environment in the equatorial plane (Liu et al .…”
mentioning
confidence: 97%
“…, Stefaniak et al . ). Synchrotron X‐ray imaging and spectromicroscopy have been used previously to analyse uranium debris.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…However, UOF 4 was detected by FT-IR following hydrolysis of UF 6 conducted in an argon matrix, a potential trap for reaction intermediates, or in solid films of UF 6 /H 2 O mixtures prepared at 12 K and slowly annealed to 242 K [5,18]. Raman spectra collected from UF 6 hydrolysis products on stainless silver foil, stainless steel, or goldcoated silicon wafers revealed that the signals from UO 2 F 2 products were enhanced compared to the signals from UO 2 F 2 products deposited on graphite [19].…”
Section: *Manuscriptmentioning
confidence: 99%